Design of Smart Green House Using pH and Water Temperature Optimization in Lettuce, Hydraulic Plant Media based on Arduino Uno - Weisrawei, Yosef; Prasetya, Dwi Arman; Setiawan, Aries Boedi (Internet of Things and Artificial Intelligence Journal, 2021)
In terms of cultivating lettuce using hydroponic media there are several things that mustbe considered such as pH levels, water temperature and sufficient light requirements.Manually checking is done so badly by the farmer that it takes a lot of time, therefore an automation system is needed in this case to overcome routine checks. This system is an alternative to modern control systems to optimize the control of pH levels, water temperature of Arduino-based lettuce plants, and the addition of a 40 watt LED lamp, pH measurement using the SEN0161 pH sensor, for measuring water temperature using the Ds18b20 sensor. Control of pH and water temperature is carried out automatically, using a peltier as a coolant and a selenoid valve as a dropping liquid pH until it reaches the required value, i.e., a pH level of 6.0-7.0, a water temperature <27 ° C and a 40 watt LED lamp as an addition to light intake in plants The stability of water temperature and pH levels that are always maintained by this tool can save time for farmers in routine checking of pH and water temperature, this tool also produces better growth of lettuce compared to the usual method.